CD39/CD73 Dysregulation of Adenosine Metabolism Increases Decidual Natural Killer Cell Cytotoxicity: Implications in Unexplained Recurrent Spontaneous Abortion - Zhu, Jianan; Song, Guangmin; Zhou, Xiaobo; Han, Ting-Li; Yu, Xinyang; Chen, Hao; Mansell, Toby; Novakovic, Boris; Baker, Philip N.; Cannon, Richard D.; Saffery, Richard; Chen, Chang; et al. (Frontiers in Immunology, 2022)
Unexplained recurrent spontaneous abortion (URSA) is believed to be associated with impaired immunosuppression at the maternal-fetal interface, but the detailed molecular mechanism remains unclear. The ATP-adenosine metabolic pathway regulated by CD39/CD73 has recently been recognized as an important mechanism in immunosuppression. The purpose of this study was to investigate the regulation of decidual natural killer (dNK) cells and fetal extravillous trophoblast (EVT) cells by CD39 and CD73 in URSA, as well as the possible regulatory mechanism of CD39/CD73 via the TGF-β-mTOR-HIF-1α pathway in clinical samples and cell models. Fewer CD39+ and CD73+ cells were found in the URSA decidual and villous tissue, respectively. Inhibition of CD39 on dNK cells transformed them to an activated state with increased toxicity and decreased apoptosis, and changed their secretion of cytokines, leading to impaired invasion and proliferation of the co-cultured HTR8/SVneo cells. Similarly, inhibition of CD73 on HTR8/SVneo cells decreased the adenosine concentration in the cell culture media, increased the proportion of CD107a+ dNK cells, and decreased the invasion and proliferation capabilities of the HTR8/SVneo cells. In addition, TGF-β triggered phosphorylation of mTOR (mammalian target of rapamycin) and Smad2/Smad3, which subsequently activated hypoxia-inducible factor-1α (HIF-1α) to induce the expression of CD73 on the HTR8/SVneo cells. In summary, reduced numbers of CD39+ and CD73+ cells at the maternal-fetal interface, which due to a downregulated TGF-β-mTOR-HIF-1α pathway, may result in reduced ATP-adenosine metabolism and increase dNK cytotoxicity, and consequently contribute to URSA occurrences.